Siamese Pumpkin Juice (Sechium Edule (Jacq.) Sw) To Decreased Blood Pressure Of Postpartum Mother's Hypertension - Anida Izatul Islami; Sri Sumarni; Djamaluddin Ramlan (Poltekkes Kemenkes Surakarta, 2022)
Background: Postpartum hypertension is Indonesia's second-highest cause of maternal death. The abundant Siamese pumpkin, commonly consumed and containing potassium (167.1 mg) and flavonoids, has a role as an antihypertensive. The proper, easy, and correct dosage must be found to utilize postpartum maternal hypertension therapy. Methods: Quay's experiment research, randomized pretest-posttest with control group design, consisted of 3 research groups, consisting of 2 intervention groups and 1 control group. Intervention I juiced 501.3 mg once daily plus antihypertensive drugs, Intervention II juiced 584,85 mg once daily plus antihypertensive drugs, and control consumed antihypertensive drugs. The sampling technique used total samples with a retrieval time of 1.5 months and obtained 16 respondents in each group. The intervention begins on the first to the fifth day of the puerperium. Bivariate analysis of systolic and diastolic blood pressure using Repeated Measure Anova. Results: The intervention group I significant decrease in systolic blood pressure and diastolic blood pressure (p-value 0.000) and intervention group II significant decrease in systolic blood pressure and diastolic blood pressure (p-value 0.000). Conclusion: Formula Siamese pumpkin juice (584,85 mg) effectively decreased blood pressure in postpartum hypertension patients.